A randomized double-blinded sham-controlled cross-over trial of tined-lead sacral nerve stimulation testing for chronic constipation. Issue 6 (June 2019) - Yiannakou, Yan; Etherson, Kevin; Close, Helen; Kasim, Adetayo; Mercer-Jones, Mark; Plusa, Stefan; Maier, Rebecca; Green, Susan; Cundall, Jeremy; Knowles, Charles; Mason, James
Abstract : Objectives: Sacral nerve stimulation (SNS) may provide long-term symptom relief to patients suffering from chronic constipation. Patients are currently selected for SNS using a 2-week peripheral nerve evaluation (PNE) comprising stimulation by temporary leads. However, only 40% of test responders receive long-term benefit from treatment meaning that healthcare costs per successfully treated patient are too high. The primary objective was to assess tined-lead testing to predict benefit from SNS for chronic constipation. Patients and methods: A randomized double-blind sham-controlled cross-over design evaluated enhanced PNE (ePNE) using tined quadripolar electrode leads over 6 weeks. The design differentiated between patients with discriminate and indiscriminate responses to testing. A score improvement of 25% or more was considered to be a positive response within a stimulation period. The primary outcome was the proportion of patients showing a reduction of at least 0.5 in constipation symptom score at 6 months. Results: A total of 45 patients were randomized, of whom 29 (64.4%) were test-phase responders. Of these, 27 were implanted providing permanent SNS. During ePNE, seven (18%) were discriminate responders, 22 (56%) were indiscriminate responders and 10 (26%) were nonresponders. Six patients were withdrawn during the test phase because of infection or noncompliance. At 6 months, there was no significant difference in primary outcome between discriminate and indiscriminate responders (60 vs. 57%, P=0.76). The study was terminated prematurely because of a persistent infection rate of 10 (22%) during ePNE of which nine (20%) were severe. Conclusion: ePNE is a poor predictor of treatment response at 6 months. This suggests a strong and persistent placebo response during both SNS PNE and treatment. An extended 6-week PNE poses a high risk of infection.